THE READABILITY OF IMAGES (AND) OF HISTORY: laudatio on the occasion of the awarding of the adorno prize (2015) to georges didi-huberman. Issue 4 (4th July 2018) - Weigel, Sigrid; Rys, Michiel; Vanvelk, Jan
Abstract: This text was delivered as the laudatory speech on the occasion of Didi-Huberman's receipt of the Adorno prize in 2015. The influence of Adorno's work on Didi-Huberman's methodology is clarified, especially Adorno's reflections on montage, the essayistic style and the anachronism of time. Didi-Huberman thematizes and analyses anachronism as a specific time structure of images. His works stress the similarity of images with the literary montage technique to develop a comprehensive theory of the readability of images ( Lesbarkeit von Bildern ) – a practice in which we approach images, based on the combination of voir and savoir, of looking and knowing. Two books, dealing with images and the Holocaust, are specifically exemplary of this approach: Images in Spite of All (2003/2008) and Bark (2011/2017). Images in Spite of All calls a halt to one of the crudest erroneous readings of Adorno's work, since the theorem of the Unspeakable or Unrepresentable always referred to Theodor W. Adorno (next to such authors as Lyotard, Blanchot, George Steiner, etc.); and it is remarkably resistant to nuanced philological–philosophical studies of Adorno's writings. By attentively considering the conditions in which the four photographs taken in Auschwitz-Birkenau were produced, Didi-Huberman dares to imagine the unimaginable. In this and in his more personal work of Bark, he successfully avoids an impossible reconstruction but instead asks what happened in that other place, in the cultural and our personal and memory. This is the work of 'readability' in the Benjaminian sense.